Pushing back : women-of-color-led grassroots activism in New York City - Rotramel, Ariella (Since 1970., 2020)
"This book explores women of color's grassroots leadership in organizations that are not singularly identified with feminism. Centered in New York City, Pushing Back brings an intersectional perspective to communities of color as it addresses injustices tied to domestic work, housing, and environmental policies and practices. Ariella Rotramel shows how activists respond to injustice and marginalization, documenting the ways people of color and the working class in the United States recognize identity as key to the roots of and solutions to injustices such as environmental racism and gentrification. Rotramel further provides an in-depth analysis of the issues that organizations representing transnational communities of color identify as fundamental to their communities and how they frame them. Introducing the theoretical concept of "queer motherwork," Rotramel explores the forms of advocacy these activists employ and shows how they negotiate internal diversity (gender, race, class, sexuality, etc.) and engage broader communities, particularly as women-led groups. Pushing Back highlights case studies of two New York-based organizations, the pan-Asian/American CAAAV: Organizing Asian Communities (formerly the Committee Against Anti- Asian Violence) and South Bronx's Mothers on the Move/ Madres en Movimiento (MOM). Both organizations are small, women-led community organizations that have participated in a number of progressive coalitions on issues such as housing rights, workers' rights, and environmental justice at the local, national, and global levels"--